2016 IEEE International Conference on Robotics and Automation (ICRA) 2016
DOI: 10.1109/icra.2016.7487649
|View full text |Cite
|
Sign up to set email alerts
|

Motion-based detection and tracking in 3D LiDAR scans

Abstract: Robots are expected to operate autonomously in increasingly complex scenarios such as crowded streets or heavy traffic situations. Perceiving the dynamics of moving objects in the environment is crucial for safe and smart navigation and therefore a key enabler for autonomous driving. In this paper we present a novel model-free approach for detecting and tracking dynamic objects in 3D LiDAR scans obtained by a moving sensor. Our method only relies on motion cues and does not require any prior information about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(101 citation statements)
references
References 13 publications
1
100
0
Order By: Relevance
“…We attempt to minimize complexity through early-fusion architecture as we focus on real-time architecture for autonomous driving. However it is found that early-fusion architecture only (RGB x rgbFlow) is not capable of extracting the required features compared to Mid-Fusion which is consistent with other literature such as [27,4]. Thus we continue our experiments using Mid or Hybrid fusion.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…We attempt to minimize complexity through early-fusion architecture as we focus on real-time architecture for autonomous driving. However it is found that early-fusion architecture only (RGB x rgbFlow) is not capable of extracting the required features compared to Mid-Fusion which is consistent with other literature such as [27,4]. Thus we continue our experiments using Mid or Hybrid fusion.…”
Section: Resultssupporting
confidence: 82%
“…Motion Segmentation using LiDAR sensor: Most of LiDAR-based methods that have been used for motion segmentation problem were based on clustering methods such as [4] which predicts the points motion by methods such as RANSAC, and then clustering takes place for object-level perception. Vaquero et al [34] initially clustered vehicles points and then performed motion segmentation on the objects after matching the objects through sequential frames.…”
Section: Related Workmentioning
confidence: 99%
“…When dealing with lidar detections a tracking system is necessary in order to provide the driving direction of the objects (e.g. [20]). Here, we can reduce the input to detections on the vehicles p = (x, y) and the driving direction as orientation vector o derived from the velocity.…”
Section: A Preprocessingmentioning
confidence: 99%
“…In 3D object detection and tracking, recent works include [18], [19]. In [18], a model-free object detection scheme based on convexity segmentation is used with a Kalman filter and constant velocity motion model.…”
Section: B Object Trackingmentioning
confidence: 99%